Factors Influencing Women Of Childbearing Age To Perform Awareness In The Working Area Of The Muara Bangkahulu Health Centre, Bengkulu City - Jumita, Jumita; Saputri, Meita Tria; Sulastri, Mepi (Journal of International Public Health, 2024)
Introduction: Data from the Bengkulu Provincial Health Office found that the number of breast cancer cases in 2022 was 15 cases found in Muko-Muko Regency with 10 cases (66.7%), Bengkulu City and Central Bengkulu Regency with 2 cases (13.3%) and South Bengkulu with 1 case (6.7%). Then, in 2023 the number of breast cancer cases in Bengkulu Province became 35 cases spread across Bengkulu City with 25 cases (71.42%), Central Bengkulu Regency with 5 cases (14.3%), Muko-Muko and Kepahiang Regencies with 2 cases (5.71%) and South Bengkulu Regency with 1 case. Methods: This study was conducted in a cross sectional manner. Data collection used primary data with the research instrument was a questionnaire. The sample in this study were women of childbearing age who had an age of 20-45 years. The number of samples used in this study were 83 people. Statistical tests used chi-square and binary logistic regression. Results and Discussion: Most of the respondents had insufficient knowledge about SADARI, most of the respondents' families did not support, almost most of the respondents completed primary education, most of the respondents had never received counselling about SADARI from health workers and most of the respondents had never done SADARI. There is a relationship between knowledge, family support, education and counselling with SADARI in Women of Fertile Age in the Working Area of the Muara Bangkahulu Health Centre, Bengkulu City in 2024. Conclusion: The independent variable most associated with SADARI is family support It is hoped that the Puskesmas can work together with related parties in conducting counselling on SADARI in women of childbearing age.